LEVEL OF PHYSICAL FITNESS AND PERFORMANCE ENGINE TEENS FROM THE PERIPHERY MOSSORO – RN (Fiep Bulletin - online, 2013)
Physical fitness and motor performance variables are influenced by several factors. In children and adolescents, physical activity promotes the full development of these variables. The aim of this descriptive study was to analyze the levels of physical fitness and motor performance of 49 students (Male = 37, Women = 12), aged 10 to 13 years, participants SESC Social Project Citizen, located in Favela Wire, a of the poorest suburbs of Mossoró. - RN. As collection instrument used a portable digital scale and stadiometer brand SANNYPara assessment of nutritional status is used ¬ mass index (BMI). To evaluate the agility (Test Square) and flexibility test (bank Wells) was used protocol PROESP (2009). also, a test proposed by motor coordination. The results show that there were significant differences in physical fitness and motor performance, when groups of both sexes and different age groups.
Keywords: physical fitness; motor performance; school